HUBUNGAN LAMA MENYUSUI DENGAN STATUS GIZI BAYI USIA 6 -12 BULAN DI KECAMATAN PONTIANAK TIMUR - Chalchi Ruhita Mlatti; Rini Andriani; Muhammad In'am Ilmiawan (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
According to WHO (2019) Malnutrition is a major cause of death among children under five years of age. An estimated 13.6 million children die annually from undernutrition globally. Malnutrition in infants is caused by poor of breastfeeding. To determine the correlation between prolonged of breastfeeding towards nutritional status in infant age 6 -12 month in East Pontianak. This research is a descriptive analytic with case control research design are 88 infant in East Pontianak as the total subjects and divided into 44 cases and 44 control. The result of this research was analyzed with mantel haenszel odd ratio testusing SPSS ver 23.0 Results 6 months old infants who received further breastfeeding can reduce the risk of malnutrition 5,1 times. There is a significant correlation between duration of breastfeeding practice towards nutritional status in infant age 6 -12 month in East Pontianak.Keywords: Nutritional status, prolonged breastfeeding, infant, breastfeeding frequency